Evaluasi Kualitas Pelayanan Halte Terminal Purabaya Pada Transportasi Umum Suroboyo Bus - Wibisono, R Endro; Putri , Rachma Febrianty (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2022)
Public transportation stops or commonly called bus stops are an integral part of the urban transportation system and part of the transportation infrastructure that is very important and needed by the community to change modes of transportation and reach other public transportation, especially the Purabaya Terminal Stop on the Suroboyo Bus public transportation. Various problems at the Purabaya Terminal stop are inadequate, such as unsafe and uncomfortable seating facilities at the bus stop, the cleanliness of the bus stop is not guaranteed, and the bus stop is not by its function and use because it is used for street vendors, two-wheeled hangouts, and others. The purpose of this observation is to determine the quality of service provided by the Purabaya Terminal Stop on Suroboyo Bus public transportation and to develop a design concept for the Suroboyo Bus stop that is environmentally friendly in the city of Surabaya. Data collection methods were used, namely field observations, literature and literature, documentation methods, and questionnaire methods. The results of this observational analysis are performance level assessment, importance level assessment, suitability level assessment, calculation of the average value of performance level and importance level, Cartesian diagram, and implementation of the IPA (Importance-Performance Analysis) method. With the results of the analysis, it can be concluded that the service quality of the Purabaya Terminal Stop on Suroboyo Bus public transportation is unsatisfactory with the performance level value of all attributes (X) of 2.89 and the importance level of all attributes (Y) of 4.81. Attributes that exist in Quadrant A (Main Priority) should be prioritized and improved so that the performance/implementation is increasing and getting better. The attributes that exist in Quadrant A are the real/physical condition of the lighting at the bus stop (Attribute number 3), the real/physical condition of the information board at the bus stop (Attribute number 4), the condition of the availability of the trash can at the bus stop (Attribute number 5), accessibility/convenience for disabled bus stop users (wheelchair users and so on) (Attribute number 10), and security guarantees from criminal acts for bus stop users (Attribute number 13). The design concept of the environmentally friendly Suroboyo Bus stop in the city of Surabaya by prioritizing the concept of green infrastructure that is environmentally friendly. Then provide facilities at the bus stop such as toilets, trash cans, seats, lighting, shade plants, green lanes (parks), pedestrian/pedestrian paths, shelter information boards, routes, and schedules (timetable) that are good and adequate at each Suroboyo Bus stop in Surabaya City.